Analisis Pendapatan Pedagang Kaki Lima Makanan dan Minuman Sektor Informal di Kecamatan Tanjung Karang Timur Kota Bandar Lampung - Ronaldo Darmawan Putra; Ida Budiarty (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This study aims to determine the effect of sales, capital, wages, raw material costs and energy costs on the income of food and beverage street vendors in the informal sector in Tanjung Karang Timur District, Bandar Lampung City. The method used in this research is a quantitative approach. This study uses primary data obtained through structured interviews. Sampling using non-probability sampling technique, and obtained as many as 50 samples of traders. The analysis technique used in this study is multiple linear regression using Eviews 10 software. The results of this study show that partially sales, capital and wages have a positive and significant effect on trader income, while wages, raw material costs and energy costs have a negative and negative effect. significant to income. The variables of sales, capital, wages, raw material costs and energy costs together have a significant effect on traders' income.